A multidisciplinary study of a burnt and mutilated assemblage of human remains from a deserted Mediaeval village in England. (December 2017) - Mays, S.; Fryer, R.; Pike, A.W.G.; Cooper, M.J.; Marshall, P.
Abstract: This work is a study of an assemblage of disarticulated human skeletal remains from a pit on the Mediaeval village site of Wharram Percy, England. The remains show evidence of perimortal breakage, burning and tool marks. The purpose of the study is to attempt to shed light on the human activity that might have produced the assemblage. The remains are subject to radiocarbon dating, strontium isotope analysis, and gross and microscopic osteological examination. The assemblage comprises 137 bones representing the substantially incomplete remains of a minimum of ten individuals, ranging in age from 2‐4 yrs to > 50 yrs at death. Both sexes are represented. Seventeen bones show a total of 76 perimortem sharp-force marks (mainly knife-marks); these marks are confined to the upper body parts. A minimum of 17 bones show evidence for low-temperature burning, and 6 long-bones show perimortem breakage. The radiocarbon dates centre on ca. 11th–13th century CE, and the remains represent the residua of more than one event. Strontium isotopic analyses of dental enamel are consistent with a local origin. Possible behaviours that may have produced the assemblage include starvation cannibalism and apotropaic efforts to lay revenant corpses. Highlights: A study of an assemblage of disarticulated human skeletal remains from a pit on the Mediaeval village site of Wharram Percy, England. The remains show evidence of perimortal breakage, burning, and knife- and chop-marks. The radiocarbon dates centre on ca. 11th–13th century AD; the remains represent the residua of more than one event. Strontium isotopic analyses of dental enamel are consistent with a local origin. Possible behaviours that may have produced the assemblage include starvation cannibalism and apotropaic efforts to lay revenant corpses.